Principalship experiences on inclusive education: a systematic review - Li, Sha; Omar, Muhd Khaizer (Scientific Research Publishing, 2024)
Inclusive education has been attracting worldwide attention and governments as well as researchers around the world. The principals’ role in embraking inclusive education spirit has become the forefront in education agenda. Therefore, this study explores and analyzes principals’ experiences in building the capacity of inclusive education at myriad school settings using Systematic Literature Review (SLR) approach. This research reviewed 75 articles within the 2010 to 2023 publication years. The sources of database derived from WOS, SCOPUS, and ERIC. Selected articles were systematically reviewed and analyzed to understand the current trends on inclusive education at the school milieu. It will advance the growth of inclusive education and widen the research’s vantage point on related topics.